Ultrasonographic Study of Gallbladder Wall Thickness and Emptying in Cirrhotic Patients without Gallstones. (29th July 2009) - Loreno, Massimiliano; Travali, Salvatore; Bucceri, Anna Maria; Scalisi, Giuseppe; Virgilio, Carla; Brogna, Alfio
Abstract : Background and Aim . Gallbladder wall thickening and impaired contractility are currently reported in cirrhotic patients and often related to portal hypertension and hepatic failure. The purpose of this work was to evaluate, by ultrasonographic method, gallbladder wall thickness and gallbladder emptying after a standard meal in normal subjects and in patients with compensated liver cirrhosis without gallstones. Methods . Twenty-three patients with Child-Pugh class A liver cirrhosis and twenty healthy controls were studied. Gallbladder wall thickness (GWT), gallbladder fasting volume (FV), residual volume (RV), and maximum percentage of emptying (%E) were calculated. Measurements of mean portal velocity, portal vein flow, and serum albumin were performed too. Statistical analysis was assessed by Student's " t test" for unpaired data. Results . GWT was0.60 ± 0.22  cm in cirrhotic patients and0.21 ± 0.06  cm in controls (P < . 0001 ). FV and RV were, respectively, 37.8 ± 3.7  cm 3 and21.8 ± 3  cm 3 in cirrhotic patients, 21.9 ± 4.2  cm 3 and4.6 ± 2.2  cm 3 in healthy volunteers (P < . 0001 ). %E was smaller in cirrhotics (42.6 ± 7.8 ) as compared to controls (80.3 ± 7.2 ;P < . 0001 ). Conclusions . In patients with compensated liver cirrhosis without gallstones gallbladder wall thickness is increased whereas its contractility is reduced. These early structural and functional alterations could play a role in gallstone formation in more advanced stages of the disease.